Simulation Analysis of Temperature Effects on the Shear Behavior of Gassy Sand. (17th March 2022) - Yang, Guangchang; Liu, Yang; Chen, Peipei
Abstract : The gas in gassy sand is enclosed in the pores of soil skeleton mainly in the form of dissolved in water or free gas bubbles, which is considered to be a perfect equilibrium composed of soil particles, pore water, gas, temperature, and overlying pressure. If any of these elements changes, this balance will be destroyed, resulting in disturbance in its mechanical properties. It is generally assumed that the existence of closed gas bubbles will not affect the soil skeleton but increase the compressibility of pore fluid. Assuming that the closed gas bubbles follow Boyle's law and Henry's law, the relationship between pore pressure change and volume strain is established. On the basis of the constitutive model which can reflect the temperature characteristics of saturated sand proposed by the author previously, combined with the special characteristics of gassy sand, the effect of temperature effects on the shear behavior of gassy sand is preliminarily explored and analyzed. The results show that under the condition of drained shear, the increase of temperature will increase the shear strength of gassy sand, and the simulation results are in good agreement with the test data. Under the condition of undrained shear, the shear strength of loose gassy sand increases with the increase of temperature, while that of dense gassy sand decreases. Moreover, the larger the gas volume, the more obvious these phenomena tend to be. However, only qualitative simulation analysis is carried out for undrained shear, which needs further verification in combination with relevant tests.